Preparation method of aluminum-wood composite board adhesive

Through the reaction of over -lipid epoxy resin and water -based polyurethane emulsion, combined with the addition of modified Yunmu powder, the existing aluminum -wood composite plate adhesives are insufficient in environmental friendship, heat resistance and storage period. The preparation of high -performance adhesives is suitable for aluminum and wood composite plates with higher heat resistance.

CN119351030APending Publication Date: 2025-01-24CHENGDU ANDUODUO TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411166634.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing aluminum-wood composite panel adhesives have shortcomings in terms of environmental friendliness, heat resistance and long storage period, which is difficult to meet the demand for high-performance adhesives.

Method used

Hyperbranched epoxy resin prepolymer is reacted with multifunctional water-based polyurethane emulsion to form a water-based hyperbranched epoxy resin-polyurethane emulsion adhesive with self-crosslinking effect, and the adhesion is improved by adding modified mica powder The bonding strength of the agent.

Benefits of technology

The adhesives that are environmentally friendly, thermal resistance and the storage period are realized, and the intensity of the material interface of the aluminum -wood composite plate is improved, and it is suitable for places with higher thermal resistance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351030A_ABST
    Figure CN119351030A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of board adhesives, in particular to a preparation method of an aluminum-wood composite board adhesive, which comprises the following steps: S1, preparation of a hyperbranched epoxy resin prepolymer: dissolving chitin in methanol, dropwise adding ethylene glycol diglycidyl ether under the protection of nitrogen, then adding modified mica powder, and stirring to obtain the hyperbranched epoxy resin prepolymer; dropwise adding a diethylenetriamine methanol solution and ethylene glycol diglycidyl ether at the same time, and reacting to remove methanol; s2, preparation of a water-based hyperbranched epoxy resin-polyurethane emulsion: mixing the multifunctional water-based polyurethane emulsion with the hyperbranched epoxy resin prepolymer, adding a pH buffer agent, an inhibitor, a protective colloid aqueous solution, a dispersant and deionized water, stirring for reaction, cooling to room temperature, adding a thickening agent aqueous solution, and stirring to obtain the adhesive. The modified mica powder is good in compatibility with epoxy resin, and the prepared adhesive is excellent in adhesive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of board adhesives, and in particular to a method for preparing an aluminum-wood composite board adhesive. Background Art

[0002] Wood composite materials use wood or wood processing residues as raw materials, and have the advantages of being naturally renewable and biodegradable. The artificial boards made from them are widely used in various fields such as furniture, interior decoration, and even structural materials. Aluminum honeycomb panels have attracted attention from various industries due to their good compression resistance, shock absorption, sound insulation, and high strength. They are currently used as wall panels, billboards, indoor partitions, and core layers of modern furniture. Combining wood composite materials, such as fiberboard, with aluminum honeycomb panels can not only protect the aluminum honeycomb finish to a certain extent, but also combine the advantages of aluminum such as light weight, corrosion resistance, moisture resistance, sound insulation, and flame retardancy to increase the added value of wood composite materials.

[0003] Generally, the adhesives used for aluminum-wood composites include solvent-based phenolic resins, two-component epoxy resins, and hot melt adhesives (Yang Hongqi et al., Wood Industry, 2011). Solvent-based phenolic resins have the advantages of high bonding strength, heat resistance, and high wear resistance, but they are relatively brittle and usually need to be toughened with thermoplastic resins. In addition, solvent-based phenolic resins are prone to produce volatile substances such as free phenols during curing, which has a certain impact on the environment. Two-component epoxy resins are also commonly used adhesives for aluminum-wood composites, with strong bonding strength, good wear resistance and chemical stability, but the storage time after two-component preparation is short, and epoxy resins are brittle and also need to be modified. In addition, there are hot melt adhesives such as EVA or polyamide, which have problems such as easy debonding after heating and cannot be used in places with high heat resistance requirements. Therefore, there is an urgent need for a special adhesive for aluminum-wood composite panels that is environmentally friendly, has a long storage period, and is heat-resistant.

[0004] Hyperbranched polymers are dendritic polymers with a highly branched structure. Compared with linear polymers, hyperbranched polymer molecules have more branching points, less molecular chain entanglement, are not easy to crystallize, have high solubility, have less effect on the viscosity of the system, and can have many functional end groups in the molecules. After modification, the materials can be given more properties. As an important branch of hyperbranched polymers, water-based hyperbranched polymers have attracted the attention of researchers because of their good solubility in water and the ability to use water as a carrier to modify materials. The high reactivity of hyperbranched polymers is used to form water-based hyperbranched resins with a self-crosslinking structure, which has good application prospects in aluminum-wood composite panels. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an adhesive for aluminum-wood composite panels to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing an aluminum-wood composite board adhesive comprises the following steps:

[0008] S1. Preparation of hyperbranched epoxy resin prepolymer:

[0009] Dissolve 2-7 parts of chitosan in 1-6 parts of methanol, add the mixture into a three-necked flask with a stirring paddle, a thermometer and a condenser, and stir. Raise the temperature to 40° C. under nitrogen protection and begin to dropwise add 5-7 parts of ethylene glycol diglycidyl ether. After the dropwise addition of ethylene glycol diglycidyl ether, add 0.8-3 parts of modified mica powder, and simultaneously dropwise add a 50-60% by mass diethylenetriamine methanol solution, wherein the diethylenetriamine methanol solution contains 4-10 parts of diethylenetriamine. After completion, raise the temperature to 65° C. and stir for 2-4 hours. Then, remove the methanol under reduced pressure in a rotary evaporator to obtain a hyperbranched epoxy resin prepolymer.

[0010] S2. Preparation of water-based hyperbranched epoxy resin-polyurethane emulsion:

[0011] The protective colloid is configured into an aqueous solution with a mass fraction of 20%, the thickener is configured into a deionized water solution with a mass fraction of 10%, 40-56 parts of a multifunctional aqueous polyurethane emulsion are mixed with a hyperbranched epoxy resin prepolymer, a pH buffer, an inhibitor, an aqueous solution of the protective colloid, a dispersant and deionized water are added, and the mixture is stirred and reacted at 40-50° C. for 0.5-1 hour, then cooled to room temperature, and the thickener aqueous solution is added and stirred for 3-5 minutes to prepare a water-based hyperbranched epoxy resin-polyurethane adhesive.

[0012] Furthermore, the modified mica powder is prepared by the following method:

[0013] Z1. Put the mica powder into a muffle furnace and calcine for 1-2 hours at a calcination temperature of 500-700° C. During the calcination process, a mixed gas of nitrogen and carbon dioxide is introduced, and the volume ratio between nitrogen and carbon dioxide is 8:1;

[0014] Z2, dispersing the mica powder calcined in step Z1 into a mixed solution of methyltriethoxysilane, ethanol and deionized water, and soaking for 0.5-3h, and heating the mixed solution to 50-70°C during the soaking process;

[0015] Z3. Filter the mixed solution in step Z2 to obtain a filtered product, wash the filtered product with deionized water and then vacuum dry it at 20°C to obtain a dried product, disperse the dried product in a mixed solution of sodium acetate, hexadecylammonium bromide and deionized water and soak it for 1-2 hours, then filter it, wash the product with deionized water and vacuum dry it at 20°C to obtain modified mica powder.

[0016] Furthermore, the mass ratio of methyltriethoxysilane, ethanol and deionized water in step Z2 to the mica powder in step Z1 is 1:(40-50):(60-80):(3-8).

[0017] Furthermore, in step Z3, the mass ratio of sodium acetate, hexadecyl ammonium bromide, dried product and deionized water is 1:(1-2):(4-6):(80-100).

[0018] Furthermore, in step S2, the weight ratio of the hyperbranched epoxy resin prepolymer to the aqueous polyurethane emulsion is 1:(1-3).

[0019] Furthermore, the pH buffer is selected from one of ammonium bicarbonate, ammonium oxalate, and ammonium dihydrogen phosphate; the inhibitor is selected from one of sodium p-hydroxybenzoate, caprolactam, and sodium bisulfite; the protective colloid is polyvinyl alcohol; the dispersant is alkylphenol polyoxyethylene ether; and the thickener is selected from alginate.

[0020] Furthermore, the model of the polyvinyl alcohol is 1778.

[0021] Furthermore, the alkylphenol polyoxyethylene ether is selected from the NP series, specifically NP-10 to NP-20.

[0022] Furthermore, the alginate is sodium alginate.

[0023] Furthermore, the multifunctional waterborne polyurethane emulsion can be purchased from Wanhua Chemical Group Co., Ltd. with a brand number of 1654.

[0024] Furthermore, the chitosan has a molecular weight of 100,000 to 200,000 and a degree of substitution greater than 80%.

[0025] Furthermore, the particle size of the mica powder is 200-800 μm.

[0026] Furthermore, the aluminum-wood composite board adhesive comprises the following components in parts by weight:

[0027] 40-56 parts of multifunctional waterborne polyurethane emulsion, 4-10 parts of diethylenetriamine, 15-35 parts of ethylene glycol diglycidyl ether, 2-7 parts of chitin, 0.8-3 parts of modified mica powder, 1-6 parts of methanol, 0.5-2 parts of pH buffer, 3-7 parts of inhibitor, 4-8 parts of protective colloid, 5-10 parts of dispersant, 2-5 parts of thickener and 50-70 parts of deionized water.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The invention uses chitosan, triamine and diglycidyl ether to react to form a water-based hyperbranched prepolymer with heat-stable chitosan and mica powder as the core and epoxy functional groups at the end, and then reacts with multifunctional water-based polyurethane to graft the prepolymer onto the polyurethane to form a water-based hyperbranched epoxy resin modified polyurethane emulsion adhesive with self-crosslinking effect, which can be used for the preparation of aluminum-wood composite panels, solving the problems of environmental protection, poor heat resistance, and short storage period;

[0030] 2. In the present invention, by adding modified mica powder therein, the modified mica powder is evenly dispersed in the emulsion, and at the same time, the modified mica powder has good compatibility with the water-based hyperbranched prepolymer with epoxy functional groups, which can effectively improve the bonding strength between the prepared water-based hyperbranched epoxy resin-polyurethane emulsion at the material interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The process flow chart of preparing the adhesive of the present invention;

[0032] Figure 2 The process flow chart of preparing modified mica powder in the present invention;

[0033] Figure 3 This is a physical picture of the adhesive prepared in Examples 1-4 of the present invention;

[0034] Figure 4 This is a physical picture of the aluminum-wood composite board of Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] See also Figures 1 to 4 , the present invention provides:

[0037] Embodiment 1:

[0038] A method for preparing a special adhesive for aluminum-wood composite panels comprises the following steps:

[0039] S1. Preparation of hyperbranched epoxy resin prepolymer:

[0040] 6 g of diethylenetriamine was dissolved in methanol in advance to prepare a diethylenetriamine methanol solution with a mass fraction of 50%, 2 g of chitosan was dissolved in methanol, and the mixture was added to a three-necked flask with a stirring paddle, a thermometer and a condenser and stirred, and the temperature was raised to 40° C. under nitrogen protection, and 6 g of ethylene glycol diglycidyl ether was added dropwise, and after the addition of 6 g of ethylene glycol diglycidyl ether, 0.8 g of modified mica powder was added, and 12 g of diethylenetriamine methanol solution and 12 g of ethylene glycol diglycidyl ether were added dropwise at the same time, and the temperature was raised to 65° C. and stirred for 2 hours, and then the methanol was removed under reduced pressure in a rotary evaporator to obtain a hyperbranched epoxy resin prepolymer;

[0041] S2. Preparation of water-based hyperbranched epoxy resin-polyurethane emulsion:

[0042] 6 g of polyvinyl alcohol 1788 was dissolved in deionized water in advance to prepare an aqueous solution with a mass fraction of 20%, 3 g of sodium alginate was dissolved in deionized water to prepare an aqueous solution with a mass fraction of 10%, 46 g of aqueous polyurethane emulsion (the functionality of the multifunctional aqueous polyurethane emulsion can be purchased from Wanhua Chemical Group Co., Ltd., with a brand of 1654, and the multifunctional aqueous polyurethane emulsion used in the following embodiments and comparative examples is the same as that used in Example 1) was mixed with 25 g of a hyperbranched epoxy resin prepolymer, 1.5 g of ammonium oxalate, 4 g of caprolactam, 30 g of a polyvinyl alcohol aqueous solution, 6 g of NP-15 and 50 g of deionized water were added, and the mixture was stirred at 50 ° C for 0.5 hour, then cooled to room temperature, 30 g of a sodium alginate aqueous solution was added and stirred for 5 min, and an aqueous hyperbranched epoxy resin-polyurethane emulsion adhesive was obtained;

[0043] The modified mica powder is prepared by the following steps:

[0044] Z1. 1.5 g of mica powder with a particle size of 400 μm was placed in a muffle furnace at 600° C. and calcined for 1.5 h. During the calcination process, a mixed gas of nitrogen and carbon dioxide with a volume ratio of 8:1 was introduced;

[0045] Z2, dispersing the mica powder calcined in step Z1 into a mixed solution of 0.3 g methyltriethoxysilane, 13 g ethanol and 22 g deionized water, and soaking for 2 hours, during which the mixed solution was heated to 65° C.;

[0046] Z3, filtering the mixed solution in step Z2 to obtain a filtered product, washing the filtered product with deionized water and vacuum drying it at 20°C to obtain a dried product, dispersing 1.2g of the dried product into a mixed solution of 0.24g of sodium acetate, 0.4g of hexadecyl ammonium bromide and 21g of deionized water and soaking it for 2h, then filtering it, washing the product with deionized water and vacuum drying it at 20°C to obtain modified mica powder. .

[0047] Embodiment 2:

[0048] A method for preparing a special adhesive for aluminum-wood composite panels comprises the following steps:

[0049] S1. Preparation of hyperbranched epoxy resin prepolymer:

[0050] Dissolve 10g of diethylenetriamine in methanol in advance to prepare a 50% by mass diethylenetriamine methanol solution, dissolve 7g of chitosan in methanol, add the mixture into a three-necked flask with a stirring paddle, a thermometer and a condenser and stir, heat the mixture to 40°C under nitrogen protection, start to drop 11.6g of ethylene glycol diglycidyl ether, add 3g of modified mica powder after dropping 11.6g of ethylene glycol diglycidyl ether, and start to drop 20g of diethylenetriamine methanol solution and 23.4g of ethylene glycol diglycidyl ether at the same time, raise the temperature to 65°C and stir for 4 hours, then remove methanol under reduced pressure in a rotary evaporator to obtain a hyperbranched epoxy resin prepolymer;

[0051] S2. Preparation of water-based hyperbranched epoxy resin-polyurethane emulsion:

[0052] 8g of polyvinyl alcohol 1788 was dissolved in deionized water in advance to prepare an aqueous solution with a mass fraction of 20%, 2g of sodium alginate was dissolved in deionized water to prepare an aqueous solution with a mass fraction of 10%, 40g of aqueous polyurethane emulsion was mixed with 40g of hyperbranched epoxy resin prepolymer, 0.5g of diammonium phosphate, 7g of sodium p-hydroxybenzoate, 40g of polyvinyl alcohol aqueous solution, 10g of NP-10 and 70g of deionized water were added, and the mixture was stirred at 40°C for 1 hour, then cooled to room temperature, 20g of sodium alginate aqueous solution was added and stirred for 3min, and an aqueous hyperbranched epoxy resin-polyurethane emulsion adhesive was obtained;

[0053] The modified mica powder is prepared by the following steps:

[0054] Z1. 4.5 g of mica powder with a particle size of 200 μm was placed in a muffle furnace at 500° C. and calcined for 1 h. During the calcination process, a mixed gas of nitrogen and carbon dioxide with a volume ratio of 8:1 was introduced;

[0055] Z2, dispersing the mica powder calcined in step Z1 into a mixed solution of 1.5 g methyltriethoxysilane, 60 g ethanol and 120 g deionized water, soaking for 0.5 h, and heating the mixed solution to 50° C. during the soaking process;

[0056] Z3. Filter the mixed solution in step Z2 to obtain a filtered product, wash the filtered product with deionized water and then vacuum dry it at 20°C to obtain a dried product, disperse 3.6 g of the dried product in a mixed solution of 0.9 g of sodium acetate, 0.9 g of hexadecylammonium bromide and 72 g of deionized water, and soak it for 1 hour, then filter it, wash the product with deionized water and vacuum dry it at 20°C to obtain modified mica powder.

[0057] Embodiment 3:

[0058] A method for preparing a special adhesive for aluminum-wood composite panels comprises the following steps:

[0059] S1. Preparation of hyperbranched epoxy resin prepolymer:

[0060] 4 g of diethylenetriamine was dissolved in methanol in advance to prepare a 50% by mass diethylenetriamine methanol solution, 5 g of chitosan was dissolved in methanol, added to a three-necked flask with a stirring paddle, a thermometer and a condenser and stirred, the temperature was raised to 40° C. under nitrogen protection, and 5 g of ethylene glycol diglycidyl ether was added dropwise, after which 5 g of ethylene glycol diglycidyl ether was added dropwise, 1.8 g of modified mica powder was added, and 8 g of diethylenetriamine methanol solution and 10 g of ethylene glycol diglycidyl ether were added dropwise at the same time, the temperature was raised to 65° C. and stirred for 3 hours, and then the methanol was removed under reduced pressure in a rotary evaporator to obtain a hyperbranched epoxy resin prepolymer;

[0061] S2. Preparation of water-based hyperbranched epoxy resin-polyurethane emulsion:

[0062] 4 g of polyvinyl alcohol 1788 was dissolved in deionized water in advance to prepare an aqueous solution with a mass fraction of 20%, 5 g of sodium alginate was dissolved in deionized water to prepare an aqueous solution with a mass fraction of 10%, 56 g of aqueous polyurethane emulsion was mixed with 20 g of hyperbranched epoxy resin prepolymer, 2 g of ammonium bicarbonate, 3 g of sodium bisulfite, 20 g of polyvinyl alcohol aqueous solution, 5 g of NP-20 and 60 g of deionized water were added, and the mixture was stirred at 40 ° C for 1 hour, then cooled to room temperature, 50 g of sodium alginate aqueous solution was added and stirred for 4 min, and an aqueous hyperbranched epoxy resin-polyurethane emulsion adhesive was obtained;

[0063] The modified mica powder is prepared by the following steps:

[0064] Z1. 3.2 g of mica powder with a particle size of 800 μm was placed in a muffle furnace at 700° C. and calcined for 2 h. During the calcination process, a mixed gas of nitrogen and carbon dioxide with a volume ratio of 8:1 was introduced;

[0065] Z2, dispersing the mica powder calcined in step Z1 into a mixed solution of 0.4 g methyltriethoxysilane, 20 g ethanol and 32 g deionized water, and soaking for 3 hours, during which the mixed solution was heated to 70° C.;

[0066] Z3. Filter the mixed solution in step Z2 to obtain a filtered product, wash the filtered product with deionized water and then vacuum dry it at 20°C to obtain a dry product, disperse 3g of the dry product in a mixed solution of 0.5g sodium acetate, 1g hexadecylammonium bromide and 50g deionized water and soak it for 2h, then filter it, wash the product with deionized water and vacuum dry it at 20°C to obtain modified mica powder.

[0067] Embodiment 4:

[0068] A method for preparing a special adhesive for aluminum-wood composite panels comprises the following steps:

[0069] S1. Preparation of hyperbranched epoxy resin prepolymer:

[0070] 8 g of diethylenetriamine was dissolved in methanol in advance to prepare a 50% by mass diethylenetriamine methanol solution, 4 g of chitosan was dissolved in methanol, added to a three-necked flask with a stirring paddle, a thermometer and a condenser and stirred, the temperature was raised to 40° C. under nitrogen protection, 8.3 g of ethylene glycol diglycidyl ether was added dropwise, after 8.3 g of ethylene glycol diglycidyl ether was added dropwise, 2.4 g of modified mica powder was added, and 16 g of diethylenetriamine methanol solution and 16.7 g of ethylene glycol diglycidyl ether were added dropwise at the same time, the temperature was raised to 65° C. and stirred for 2 hours, and then the methanol was removed under reduced pressure in a rotary evaporator to obtain a hyperbranched epoxy resin prepolymer;

[0071] S2. Preparation of water-based hyperbranched epoxy resin-polyurethane emulsion:

[0072] 6 g of polyvinyl alcohol 1788 was dissolved in deionized water in advance to prepare an aqueous solution with a mass fraction of 20%, 4 g of sodium alginate was dissolved in deionized water to prepare an aqueous solution with a mass fraction of 10%, 50 g of aqueous polyurethane emulsion was mixed with 22 g of hyperbranched epoxy resin prepolymer, 1.5 g of ammonium bicarbonate and 0.5 g of ammonium oxalate, 4 g of caprolactam, 30 g of polyvinyl alcohol aqueous solution, 3 g of NP-10, 4 g of NP-20 and 60 g of deionized water were added, and the mixture was stirred at 40 ° C for 1 hour, then cooled to room temperature, 40 g of sodium alginate aqueous solution was added and stirred for 4 min, and an aqueous hyperbranched epoxy resin-polyurethane emulsion adhesive was obtained;

[0073] Z1. 4.2 g of mica powder with a particle size of 400 μm was placed in a muffle furnace at 550° C. and calcined for 1.5 h. During the calcination process, a mixture of nitrogen and carbon dioxide with a volume ratio of 8:1 was introduced;

[0074] Z2, dispersing the mica powder calcined in step Z1 into a mixed solution of 0.7 g methyltriethoxysilane, 31 g ethanol and 46 g deionized water, and soaking for 2 h, during which the mixed solution was heated to 60° C.;

[0075] Z3. Filter the mixed solution in step Z2 to obtain a filtered product, wash the filtered product with deionized water and then vacuum dry it at 20°C to obtain a dried product, disperse 3.6 g of the dried product in a mixed solution of 1 g of sodium acetate, 1.5 g of hexadecylammonium bromide and 95 g of deionized water, and soak it for 1.5 h, then filter it, wash the product with deionized water and vacuum dry it at 20°C to obtain modified mica powder.

[0076] Comparative Example 1

[0077] The difference between Comparative Example 1 and Example 1 is that the modified mica powder added in step S1 is replaced by unmodified mica powder, and the remaining steps are exactly the same as those in Example 1.

[0078] Comparative Example 2

[0079] A commercially available two-component epoxy resin was used as a comparative experiment.

[0080] Specific experiments

[0081] The adhesives obtained in Examples 1-4 and Comparative Examples 1-2 were applied to the surface of the aluminum honeycomb panel using a coating roller, with a wet coating amount of 30 g / m 2 The aluminum honeycomb panel and the medium density fiberboard were hot pressed at a pressure of 0.4 MPa and a temperature of 120°C for 9 minutes, and then placed at room temperature for 36 hours to obtain an aluminum-wood composite panel;

[0082] Referring to the national standard "Test Methods for Physical and Chemical Properties of Artificial Boards and Facing Artificial Boards" (GB / T17657-2022), Examples 1-4 and Comparative Examples 1-2 were boiled in water at 100°C for 3 hours and the surface bonding strength was tested. The results are shown in Table 1:

[0083] Table 1: Adhesive bonding strength test table of Examples 1-4 and Comparative Examples 1-2

[0084] Surface bonding strength (MPa) Example 1 1.44 Example 2 1.81 Example 3 1.60 Example 4 1.65 Comparative Example 1 1.15 Comparative Example 2 Glue opening

[0085] The results show that the aluminum-wood composite board prepared in Comparative Example 1 debonds after being boiled in water at 100°C for 3 hours, indicating that the boiling water resistance of Comparative Example 1 is poor, while the surface bonding strength of Examples 1-4 after being boiled in water at 100°C for 3 hours is 1.44-1.81 MPa, which has good boiling water resistance and can be used in places requiring high heat resistance. In addition, the data of Example 1 and Comparative Example 1 show that the surface bonding strength of the present invention is also improved by adding modified mica powder compared with ordinary mica powder.

[0086] The above embodiments demonstrate the application of the present invention in aluminum-wood composite panels. The water-based hyperbranched epoxy resin-polyurethane emulsion adhesive prepared by the present invention can also be used for the composite of wood and other metal plates, such as iron plates, copper plates, etc.; the water-based hyperbranched epoxy resin-polyurethane emulsion adhesive can also be used for wood impregnation modification after dilution; the water-based hyperbranched epoxy resin-polyurethane emulsion adhesive can also be compounded with wood modifiers such as paraffin waterproofing agents, CCA wood preservatives, etc.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an aluminum-wood composite board adhesive, characterized in that: Use the following steps: S1. Preparation of hyperbranched epoxy resin prepolymer: Dissolve 2-7 parts of chitosan in 1-6 parts of methanol, add the mixture into a three-necked flask with a stirring paddle, a thermometer and a condenser, and stir. Raise the temperature to 40° C. under nitrogen protection and begin to dropwise add 5-7 parts of ethylene glycol diglycidyl ether. After the dropwise addition of ethylene glycol diglycidyl ether, add 0.8-3 parts of modified mica powder, and simultaneously dropwise add a 50-60% by mass diethylenetriamine methanol solution, wherein the diethylenetriamine methanol solution contains 4-10 parts of diethylenetriamine. After completion, raise the temperature to 65° C. and stir for 2-4 hours. Then, remove the methanol under reduced pressure in a rotary evaporator to obtain a hyperbranched epoxy resin prepolymer. S2. Preparation of water-based hyperbranched epoxy resin-polyurethane emulsion: The protective colloid is configured into an aqueous solution with a mass fraction of 20%, the thickener is configured into a deionized water solution with a mass fraction of 10%, 40-56 parts of a multifunctional aqueous polyurethane emulsion are mixed with a hyperbranched epoxy resin prepolymer, a pH buffer, an inhibitor, an aqueous solution of the protective colloid, a dispersant and deionized water are added, and the mixture is stirred and reacted at 40-50° C. for 0.5-1 hour, then cooled to room temperature, and the thickener aqueous solution is added and stirred for 3-5 minutes to prepare a water-based hyperbranched epoxy resin-polyurethane adhesive.

2. The method for preparing the aluminum-wood composite board adhesive according to claim 1, characterized in that: The modified mica powder is prepared by the following method: Z1. Put the mica powder into a muffle furnace and calcine for 1-2 hours at a calcination temperature of 500-700° C. During the calcination process, a mixed gas of nitrogen and carbon dioxide is introduced, and the volume ratio between nitrogen and carbon dioxide is 8:1; Z2, dispersing the mica powder calcined in step Z1 into a mixed solution of methyltriethoxysilane, ethanol and deionized water, and soaking for 0.5-3h, and heating the mixed solution to 50-70°C during the soaking process; Z3. Filter the mixed solution in step Z2 to obtain a filtered product, wash the filtered product with deionized water and then vacuum dry it at 20°C to obtain a dried product, disperse the dried product in a mixed solution of sodium acetate, hexadecylammonium bromide and deionized water and soak it for 1-2 hours, then filter it, wash the product with deionized water and vacuum dry it at 20°C to obtain modified mica powder.

3. The method for preparing the aluminum-wood composite board adhesive according to claim 2, characterized in that: The mass ratio of methyltriethoxysilane, ethanol and deionized water in step Z2 to the mica powder in step Z1 is 1:(40-50):(60-80):(3-8).

4. The method for preparing the aluminum-wood composite board adhesive according to claim 2, characterized in that: In the step Z3, the mass ratio of sodium acetate, hexadecyl ammonium bromide, dried product and deionized water is 1:(1-2):(4-6):(80-100).

5. The method for preparing the aluminum-wood composite board adhesive according to claim 1, characterized in that: In the step S2, the weight ratio of the hyperbranched epoxy resin prepolymer to the aqueous polyurethane emulsion is 1:(1-3).

6. The method for preparing the aluminum-wood composite board adhesive according to claim 1, characterized in that: The pH buffer is selected from one of ammonium bicarbonate, ammonium oxalate and diammonium phosphate.

7. The method for preparing the aluminum-wood composite board adhesive according to claim 1, characterized in that: The inhibitor is selected from one of sodium p-hydroxybenzoate, caprolactam and sodium bisulfite.

8. The method for preparing the aluminum-wood composite board adhesive according to claim 1, characterized in that: The protective colloid is polyvinyl alcohol, and the dispersant is alkylphenol polyoxyethylene ether.

9. The method for preparing the aluminum-wood composite board adhesive according to claim 1, characterized in that: The thickener is selected from alginate.

10. The method for preparing the aluminum-wood composite board adhesive according to claim 1, characterized in that: In step S2, the pH buffer is used in an amount of 0.5-2 parts; the inhibitor is used in an amount of 3-7 parts; the protective colloid is used in an amount of 4-8 parts; the dispersant is used in an amount of 5-10 parts; the thickener is used in an amount of 2-5 parts; and the deionized water is used in an amount of 50-70 parts.